Optimization of durability properties of concrete containing fly ash using Taguchi's approach and Anova analysis - Uysal, Mucteba; Akyuncu, Veysel; Tanyildizi, Harun; Sumer, Mansur; Yildirim, Hasan (Pontificia Univ Catolica Chile, Escuela Construccion Civil, 2018)
In this study, optimization of durability properties of the concretes was performed by using Taguchi method and Anova analysis. The durability performance of the concretes was evaluated using measurements of rapid chloride ion permeability, freezing-thawing resistance and sorptivity tests. The degree of freezing-thawing resistance was assessed the change of weight, ultrasonic pulse velocity (UPV) and flexural strength after 300 cycles. The use of fly ash improved the rapid chloride ion permeability and sorptivity of concrete. The best resistance to chloride ion permeability was obtained from a combination of type of class C fly ash content of 102 kg/m(3) with PC content of 332 kg/m(3). There was a remarkable reduction in the UPV after the specimens are subjected to freezing-thawing cycles. The amounts of flexural strength loss have been measured in the range of 6.70 - 29.83%. The use of type of class C fly ash positively affected freezing-thawing resistance of concrete. The Anova analysis indicated that the cement dosage has an utmost importance on the sorptivity level, chloride ion permeability and ultrasonic pulse velocity loss. Furthermore, the fly ash percentage has an utmost importance on the weight loss and flexural strength loss.
Optimización de las propiedades de durabilidad del hormigón que contiene ceniza, utilizando el enfoque Taguchi y análisis Anova
Keywords: Type of class C fly ash; sorptivity; Chloride ion permeability; freezing-thawing resistance